Value Of Experience, Satisfaction, Love, Brand Loyalty and Behavior Intentions With Generation as Moderating Variable: Nilai Pengalaman, Kepuasan, Kecintaan, Kesetiaan Merek dan Niat Perilaku Dengan Generasi Sebagai Moderasi - Sabella, Jenny; Sitohang, Ellen Theresia (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to understand the condition of BSI employees as one of the impacts during the first year of the merger process. This research and writing is also motivated by the idea that a business organization certainly wants optimal performance. In order for the organization to provide optimal performance, the thing that must be strengthened is the Human Resources (HR) as an asset and the company's internal customers. Study uses SPSS 17.0 and WarpPLS 7.0 as analysis tools. The reason for using WarpPLS 7.0 is because it can be used for large respondents and this is statistics for analyzing several research variables simultaneously and can be used for research using primary data using the survey method. The number of respondents in this study were 118 people spread throughout Indonesia. The consideration for the justification for using the number of respondents is based on the theory (Sholihin, 2020a) that the minimum sample size for SEM-PLS must be equal to or greater than (1) ten times the largest number of formative indicators used or (2) ten times the number of pathways largest structural unit regarding a particular construct in the structural model. The majority of respondents argue that the value of employee experience can influence employee satisfaction, and employee satisfaction with BSI influences employee love and loyalty for BSI which encourages employee intentions to be active in BSI's internal organization. Respondents also agreed with the hypothesis which states that the moderating generation affects the value of experience on employee satisfaction. Implications: this study also confirms previous research that satisfaction can affect the love and loyalty of a brand. This study also confirms that the majority of respondents agree that the value of employee experience can affect employee satisfaction, and employee satisfaction with BSI affects employee love and loyalty to BSI which encourages employees' intention to be active in BSI's internal organization. the practical implication is that the behavior of employees to be active in BSI's internal organization can be a medium that strengthens relations between employees. Variable value of employee experience and variable intention of planned behavior to join an internal organization as a novelty / novelty.